DISTRIBUTION AND STRUCTURE CENOPOPULATIONS OF A RARE, ENDEMIC PLANT ALLOCHRUSA GYPSOPHILOIDES (REGEL) SCHISCHK. IN SOUTHERN KAZAKHSTAN (Experimental biology, 2022)
The article describes the features of the structure of cenopopulations and the distribution of the rare, endemic plant Allochrusa gypsophiloides. 3 populations, 4 cenopopulations were studied. At the same time, a map-scheme on plant species distribution was drawn up between 2011 and 2022.A DEM map was created for the distribution zones of the 3 populations found in the study. The average species density varied from 1.5 to 2.9 pcs.Cenopopulation - the dominance of generative individuals 1, 2 and 3,4 corresponds to the state of CP-1 - absolute maximum g1(20,0%), cenopopulation 2-3 and 4- varies from 18,52%, 24,14% and 33,34%. The number of postgenerative individuals in the cenopopulations is not significantly high, varying within the subsenile ss (0% -13.34%).Illustrative graphs, tables on age spectrum of Allochrusa gypsophiloides species cenopopopulations were created and the current state of structural features of distribution and cenopopulations of the plant was evaluated.
Keywords: Key words: Allochrusa gypsophiloides, cenopopulation, endemic, age composition, SyrDarya Karatau, DEM map.